SOSIALISASI KURIKULUM MAGISTER PENDIDIKAN ILMU PENGETAHUAN SOSIAL (IPS) BAGI STAKEHOLDER DI KABUPATEN BIREUEN - Novalita, Rahmi; Azizah, Cut; Muharramsyah, Rambang; Zahara, Zahara (Universitas Nusa Bangsa, 2022)
AbstractCommunity service activities began with the problem of limited S1 graduates in the Social Education field to continue their education to the postgraduate level in Aceh Province, especially in Bireuen Regency. The objectives of community service activities are 1) as a manifestation of the Tridarma of Higher Education lecturers in the Social Science Education Study Program, Postgraduate Program, Almuslim University, 2) to provide feedback on curriculum development by stakeholder needs before it is implemented. The implementation of community service activities was carried out at the Ampon Check Peusangan Hall, Almuslim University. The results of community service activities included stakeholders strongly supporting the sustainability of the Social Science Education Study Program, Postgraduate Program, Almuslim University in improving the quality of education in Aceh Province, especially Bireuen Regency. The service results were a curriculum draft for the Social Studies Education Study Program.AbstrakKegiatan pengabdian kepada masyarakat berawal dari permasalahan keterbatasan lulusan S1 Bidang Ilmu Pendidikan Sosial untuk melanjutkan pendidikan ke tingkat S2 di Provinsi Aceh, terutama Kabupaten Bireuen. Tujuan kegiatan pengabdian kepada masyarakat adalah 1) Sebagai wujud Tridharma Perguruan Tinggi dosen pada Program Studi Magister Pendidikan Ilmu Pengetahuan Sosial Program Pascasarjana Universitas Almuslim, 2) Memberikan umpan balik tentang pengembangan kurikulum sesuai dengan kebutuhan stakeholder sebelum diimplementasikan. Pelaksanaan kegiatan pengabdian masyarakat dilaksanakan di Gedung Aula Ampon Check Peusangan Universitas Almuslim. Hasil kegiatan pengabdian kepada masyarakat antara lain stakeholder sangat mendukung keberlanjutan Program Studi Magister Pendidikan Ilmu Pengetahuan Sosial Program Pascasarjana Universitas Almuslim dalam meningkatkan kualitas pendidikan di Provinsi Aceh, khususnya Kabupaten Bireuen. Hasil pengabdian berupa draft kurikulum Program Studi Magister Pendidikan IPS.